Influence of varying twin-roll casting conditions on the microstructure and texture development and mechanical properties of a Mg-6.8Y-2.5Zn-0.4Zr alloy - Franziska Ueberschär; Madlen Ullmann; Ulrich Prahl (Frontiers in Metals and Alloys, 2025)
In this study the influence of varying twin-roll casting (TRC) conditions on the microstructure, texture and mechanical properties of a Mg-6.8Y-2.5Zn-0.4Zr alloy (WZ73) was investigated. In particular the twin-roll cast speed and rolling gap were varied. Post twin-roll casting, the microstructure exhibits non-uniformity across the strip thickness and consists of a network-like arrangement of the long period stacking ordered (LPSO) phases and the α-Mg matrix. The α-Mg matrix is characterized by dobulites (flake-like structures). Various defects typical for twin-roll cast strips were observed, along with a notable impact of casting conditions on the precipitation, morphology, and phase composition of the LPSO phases. The twin-roll casting speed significantly influences the resultant microstructural features. Higher casting speeds reduce the average equivalent deformation degree, leading to an increase in the phase fraction of LPSO structures but a reduction in thickness. Additionally, higher TRC speeds result in decreased solidification times, promoting inhomogeneity and segregation defects. These changes also impact the distribution of precipitates and strip temperature at the roll gap exit, delaying solidification and influencing centerline segregation thickness. Kink bands and yttrium-rich precipitates were present in all samples, with LPSO phases precipitating along grain boundaries. No dynamic recrystallization was observed. Texture analysis revealed basal and non-basal slip activation, with lower intensities at higher TRC speeds. The yield strength (YTS) and tensile strength (UTS) behaved similar whilst the elongation remained unchanged by the TRC conditions.